Presenting a conceptual model of the human as an agent based on the lived experience of successful youth labor: A grounded theory study - maryam hozhabriannazari; hossein salimibajestani; masumeh esmaili; ebrahim naeimi (مجله علوم روانشناختی)
Background: The phenomenon of child and youth labor is a multifaceted challenge encompassing biological, psychological, and social dimensions, and it has emerged as a significant concern in various countries, including Iran. However, the predominant research has often approached this issue from a social work perspective, focusing on description and pathology. There has been a notable absence of studies addressing the empowerment of this demographic to navigate and overcome challenging environmental circumstances. Given the expanding population and the substantial personal and social challenges faced by working children and adolescents, it becomes apparent that conducting research in this area could contribute to the empowerment of these individuals. Aims: The present study aimed to present the model of human as an agent based on the lived experiences of youth labore. Methods: This study employed a qualitative approach, specifically utilizing the grounded theory method. The research focused on purposefully selecting 15 successful youth laborers residing in Tehran in 2023. Participants were chosen through referrals from Toloe Bi neshanha Center, Mehr and Mah Institute, and Al Yassin Assistance Clinic. After obtaining their consent and willingness to participate in the research, they became part of the study. Data was gathered through semi-structured interviews and analyzed using the Strauss and Corbin method. Results: The analysis of the interview data was generally categorized into seven axes: internal strength, chaotic environmental conditions, support system, learning experiences, humanistic strategies, positive and active design of life, and comprehensive and integrated growth, and finally, the conceptual model of the human as an agent based on the codes was drawn. Conclusion: The obtained results, in addition to increasing insight into the components of the human as an agent model and the factors behind its creation, can be used as a basis for further research and the design of educational and therapeutic programs aimed at improving the psychological capabilities of youth laborers.